Legal framework for artificial intelligence - Tancer Verboten, Mojca (Acta Medico-Biotechnica, 2025)
Artificial intelligence is becoming a reality in today’sworld, and is becoming increasingly integrated intoour lives. The development of new technologies basedon artificial intelligence is unprecedented, bringingnumerous benefits and raising many legal questions.Its use can no longer be avoided; we must familiarizeourselves with it, take advantage of its benefits, andat the same time, be aware of the challenges it brings.The impact of artificial intelligence can be felt in allareas of the economy from manufacturing, publicadministration, transport, science, and education. Itis also strongly present in some areas of healthcare.For its proper and safe use, it is necessary to definean appropriate legal framework that will lay thefoundation for its proper functioning and resolve legalissues that arise in in the field of artificial intelligence.